'Being a horror fan and being a feminist are often a conflicting business': Feminist horror, the opinion economy and Teeth's gendered audiences. Issue 2 (1st October 2020) - Farrimond, Katherine
Horror has long been understood as a 'bad object' in relation to its audiences. More specifically, this presumed relationship is a gendered one, so that men are positioned as the genre's natural audience, while women's engagement with horror is presented as more fractious. However, those horror films framed as feminist require a reorientation of these relations. This article foregrounds the critical reception of a 'conspicuously feminist' horror film in order to explore what happens to the bad object of horror within an opinion economy that works to diagnose the feminism or its absence in popular culture. Reviews of Teeth (2007), a 'feminist horror film' about vagina dentata, illustrate the push and pull of gendered power attached to feminist media, where empowerment is often understood in binary terms in relation to its gendered audiences. The assumed disempowerment of male audiences takes precedence in many reviews, while other narratives emerge in which Teeth becomes an educational tool that might change gendered behaviours, which directly empowers female audiences or which dupes women into believing they have been empowered. Finally, Teeth's reviews expose a language of desire and fantasy around vagina dentata as an automated solution to the embodied experiences of women in contemporary culture. Teeth's reviews, I argue, offer a valuable case study for interrogating the tensions in discourse when the bad object of horror is put to work for feminism.